Wpływy polskie w mowie ludności ukraińskiej województwa lwowskiego na przykładzie słownictwa - Kostecka-Sadowa, Anna (Slavia Occidentalis, 2019)
The aim of this study is to show some aspects of how Polish loanwords exist in Ukrainian dialects in the rural areas. While in the population from the study area, Ukrainians represent a majority, the community consists of a significant percentage of Polish inhabitants. The article analyses the names of lexical and semantic group names of kitchen utensils for food preparation used in the subdialects of the Nadsiannia boundary area. The origin of the analysed names is given together with parallels with others dialects of the Ukrainian language.